2013
DOI: 10.1371/journal.pone.0058575
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Fibroblast Growth Factor 21-Based Clinical Candidate, LY2405319

Abstract: Fibroblast growth factor 21 is a novel hormonal regulator with the potential to treat a broad variety of metabolic abnormalities, such as type 2 diabetes, obesity, hepatic steatosis, and cardiovascular disease. Human recombinant wild type FGF21 (FGF21) has been shown to ameliorate metabolic disorders in rodents and non-human primates. However, development of FGF21 as a drug is challenging and requires re-engineering of its amino acid sequence to improve protein expression and formulation stability. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
150
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 32 publications
9
150
1
Order By: Relevance
“…The native mature form of FGF21 is a 19.4 kDa protein that is cleared rapidly from circulation most likely through the kidney, and has an estimated half-life of ∼1 h in rodents and 0.5-2 h in NHPs [31], [68]. In addition to the rapid renal clearance, human FGF21 protein undergoes rapid proteolysis upon injection into animals so that the 4 N-terminal amino acid residues [69] and the C-terminal 10 amino acid residues are cleaved off [68]. In vitro studies using recombinant truncated proteins showed that while the 4 N-terminal amino acid residues are not necessary for the signaling activity, the C-terminal 10 amino acid residues are essential for binding to KLB and signaling activity [43], [70].…”
Section: Turning Fgf21 Into a Drugmentioning
confidence: 99%
See 2 more Smart Citations
“…The native mature form of FGF21 is a 19.4 kDa protein that is cleared rapidly from circulation most likely through the kidney, and has an estimated half-life of ∼1 h in rodents and 0.5-2 h in NHPs [31], [68]. In addition to the rapid renal clearance, human FGF21 protein undergoes rapid proteolysis upon injection into animals so that the 4 N-terminal amino acid residues [69] and the C-terminal 10 amino acid residues are cleaved off [68]. In vitro studies using recombinant truncated proteins showed that while the 4 N-terminal amino acid residues are not necessary for the signaling activity, the C-terminal 10 amino acid residues are essential for binding to KLB and signaling activity [43], [70].…”
Section: Turning Fgf21 Into a Drugmentioning
confidence: 99%
“…In addition to the poor pharmacokinetics, native FGF21 is unstable and prone to aggregation in solution [68], [69]. Various engineering approaches have been undertaken to enable a stable liquid formulation at high concentration with a low viscosity.…”
Section: Turning Fgf21 Into a Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Truncation of N termini (NT) by six or more residues, or C termini (CT) by two or more residues, decreased in vitro potency more than 10-fold, suggesting that potent functional activity was derived from both termini of FGF21 (Micanovic et al, 2009;Yie et al, 2009). In diabetic animal models and patients with type 2 diabetes, recombinant fibroblast growth factor 21 (rFGF21) and its analogs demonstrated dose-dependent reductions in low-density lipoprotein cholesterol, apolipoproteins, fasting triglycerides, fasting insulin, and body weight, as well as dose-dependent elevations of high-density lipoprotein cholesterol and adiponectin (Adams et al, 2013;Gaich et al, 2013;Kharitonenkov et al, 2013;Smith et al, 2013). Although dose-dependent reductions in blood glucose have been observed in diabetic rodent and nonhuman primate models, thus far only a trend toward lower fasting blood glucose has been observed in human clinical studies (Gaich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical studies do not permit clarification whether FGF21 predisposes to the development of carbohydrate disturbances or is a mechanism of ineffective compensation. Some authors suggest the use of anti-FGF receptor 1 (FGFR1) antibodies (R1MAbs) that mimic the metabolic effects of FGF21 on obesity and type 2 diabetes treatment (23,24,25,26,27).…”
Section: Introductionmentioning
confidence: 99%